Molecular Biology of Selenium in Health and Disease - Tsuji, Petra A.; Hatfield, Dolph L. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The trace mineral selenium is still regarded as one of the most interesting and health-beneficial elements. In addition to the Editorial containing a dedication to Dr. Leopold Flohé, this Special Issue contains 13 research articles and 8 reviews, with over 120 different contributors covering many of the most important subjects concerning the study of selenium. The articles address both selenium as well as selenoproteins and their molecular roles, providing important considerations regarding this trace element's impact on human and animal health and disease.